The Influence of Food Quality and Store Atmosphere on Consumer Satisfaction with Purchasing Decisions as an Intervening Variable - Ferdian Hendrastama Huda; Henny Welsa; Nonik Kusuma Ningrum (PT Mattawang Mediatama Solution, 2024)
This research aims to examine the influence of food quality and shop atmosphere on consumer satisfaction with purchasing decisions as an intervening variable (case study of Rocket Chicken in Kemusuk Sedayu Bantul). This research uses quantitative research methods. The variables in this research are food quality, store atmosphere, consumer satisfaction, and purchasing decisions. The respondents in this research were consumers at Rocket Chicken in Kemusuk Sedayu Bantul. The number of samples in this study was 200 people. The data source used is primary data. The data collection technique used was a questionnaire distributed via Google Form. Data analysis techniques use SPSS 23 which consists of validity and reliability tests, descriptive statistics, classical assumption tests, regression tests, hypothesis tests, coefficient of determination, and Sobel tests. The results of this research show that there is a positive and significant influence of food quality and shop atmosphere on consumer satisfaction with purchasing decisions as an intervening variable (Case Study of Rocket Chicken in Kemusuk Sedayu Bantul). Suggestions for future researchers to add other variables as intervening variables.